Clinical Judgment During Simulation: A Comparison of Student and Faculty Scores. Issue 2 (March 2017) - Strickland, Haley P.; Cheshire, Michelle H.; March, Alice L.
Abstract : Abstract: This study utilized the Lasater Clinical Judgment Rubric (LCJR) to investigate the relationship between the student's self-assessment of clinical judgment skills and the faculty's assessment during a human patient simulation. The study used a quantitative design with baccalaureate nursing students ( n = 94) enrolled in an adult health course as participants. The data revealed a positive correlation between evaluator and student scores on the LCJR. The findings support the use of the LCJR in combination with simulation to evaluate nursing students' clinical judgment skills and to quantify competency levels.